PEMBUATAN DINDING PEMBATAS TEMPAT PEMANDIAN UMUM DI DESA JADA BAHRIN - Yayuk Apriyanti; Endang S Hisyam; Desy Yofianti; Ferra Fahriani (Fakultas Teknik, Universitas Bangka Belitung, 2023)
Jada Bahrin Village is one of the assisted villages of the Faculty of Engineering so that the Department of Civil Engineering has in recent years been carrying out community service activities in this village. Service activities carried out at the request of the community and village officials. In 2022, a request from the community and village officials is in the form of building a dividing wall for public baths. This was conveyed by village officials because this facility is used by the community for daily activities such as bathing and washing clothes. This facility is used by many people because the availability of water in Jada Bahrin Village is still limited. The absence of adequate dividing walls makes people feel uncomfortable using this facility. With this problem, the service team intends to fulfill the wishes of this community through the survey, planning/design and implementation stages. With the construction of a dividing wall between men and women, the community feels comfortable using this public facility.